2012
DOI: 10.1371/journal.pone.0030897
|View full text |Cite
|
Sign up to set email alerts
|

Busulphan-Cyclophosphamide Cause Endothelial Injury, Remodeling of Resistance Arteries and Enhanced Expression of Endothelial Nitric Oxide Synthase

Abstract: Stem cell transplantation (SCT) is a curative treatment for malignant and non malignant diseases. However, transplantation-related complications including cardiovascular disease deteriorate the clinical outcome and quality of life. We have investigated the acute effects of conditioning regimen on the pharmacology, physiology and structure of large elastic arteries and small resistance-sized arteries in a SCT mouse model. Mesenteric resistance arteries and aorta were dissected from Balb/c mice conditioned with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 63 publications
1
23
0
1
Order By: Relevance
“…It was shown that PTN expressed from BM perivascular stromal cells plays a role in homeostatic hematopoiesis, while vascular ECs secreted PTN under BM ablation. Even though endogenous PTN can regulate hematopoiesis under injury, BM preconditioning involves damage to niche compartments including ECs, as indicated by increased levels of circulating ECs [25]. Therefore, supplementation of MSC CM and/or recombinant PTN may accelerate restoration of BM function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that PTN expressed from BM perivascular stromal cells plays a role in homeostatic hematopoiesis, while vascular ECs secreted PTN under BM ablation. Even though endogenous PTN can regulate hematopoiesis under injury, BM preconditioning involves damage to niche compartments including ECs, as indicated by increased levels of circulating ECs [25]. Therefore, supplementation of MSC CM and/or recombinant PTN may accelerate restoration of BM function.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelia play important roles in maintaining vascular homeostasis, and intercellular junctions support structural integrity and cell-to-cell communication. High-dose chemotherapy causes significant damage to the endothelium [24,25], and delayed recovery of endothelial integrity may result in defects to vascular function. Regarding HSCT, elevated levels of circulating ECs indicate endothelial damage as well as graft-versus-host disease [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…203 Diagnosing TMA in the setting of BMT/SCT is challenging because thrombocytopenia, renal insufficiency, and the presence of schistocytes may also represent other complications, such as graft versus host disease (GvHD) and systemic infections. 141,204 Endothelial cell injury, induced by chemotherapy 205 and cyclosporine, 184 a prothrombotic state 206 and additional risk factors such as intravenous catheters, infections, and GvHD may well contribute to TMA pathogenesis. 203 In addition, endothelial cell regeneration is limited, as bone marrow endothelial progenitor cell populations, the source for endothelial cell repair, are depleted by the conditioning treatments.…”
Section: Thrombotic Microangiopathy Associated With Antibody-mediatedmentioning
confidence: 99%
“…In ex vivo studies of arteries and arterioles exposed to common conditioning agents, busulfan, and cyclophosphamide, morphologic analysis revealed detachment of ECs from the basement membrane and disruption of endothelial cell–cell contact. 18 As with radiation, immediate enhanced vascular relaxation correlated with detected upregulation of eNOS that was hypothesized to be a marker of endothelial stress, although the exact mechanism remains unclear. Cyclosporin A and tacrolimus are the two calcineurin inhibitors (CNIs) that are widely used for treatment and prophylaxis of GVHD and are well known for their kidney and vascular toxicity brought on by constriction and hyperplasia of small arteries resulting in renal blood flow and glomerular filtration rate reduction.…”
Section: Mechanisms Of Endothelial Injury During Hsctmentioning
confidence: 99%